Preparation method of CN / AgInS2 heterojunction composite photocatalyst
By constructing CN/AgInS2 heterojunction composite photocatalysts, the problems of high energy consumption and insufficient performance of single-component photocatalytic carbon dioxide reduction technology are solved, and efficient photocatalytic carbon dioxide reduction performance is achieved.
Patent Information
- Application Number
- CN202411665231.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The existing photocatalytic carbon dioxide reduction technology has the characteristics of high energy consumption, difficulty in single-component photocatalysts having visible light response, high physical and chemical properties, and high carbon dioxide reduction efficiency, which limits its practical application.
Using CN/AgInS2 heterojunction composite photocatalyst, AgInS2 particles were dispersed on the CN nanolayer through electrostatic self-assembly to construct a new CN/AgInS2 heterojunction material to enhance its visible light absorption capacity, charge separation capacity and redox capacity.
It realizes efficient photocatalytic carbon dioxide reduction, improves the carbon dioxide reduction performance of the composite photocatalyst, and has efficient charge separation and redox capabilities.
Smart Images

Figure CN119500225A_ABST
Abstract
Description
Technical Field
[0001] The embodiment of the present invention relates to the field of material technology, a CN / AgInS 2 A method for preparing a heterojunction composite photocatalyst. Background Art
[0002] The current large-scale consumption of non-renewable fossil energy has not only exacerbated the crisis of energy shortage, but also significantly increased carbon dioxide emissions, breaking the balance of the carbon cycle in nature. The concentration of greenhouse gases in the atmosphere, mainly carbon dioxide, continues to increase, which intensifies the greenhouse effect of the atmosphere, leading to increasingly serious problems such as melting glaciers, rising sea levels, and aggravated natural disasters. Therefore, it is necessary to find a method that can both reduce the concentration of carbon dioxide in the atmosphere and convert it into chemical fuels.
[0003] In recent years, the use of clean, pollution-free and abundant solar energy for semiconductor photocatalytic carbon dioxide reduction has become an environmentally friendly and sustainable approach. This technology has the advantages of simple and easy-to-obtain raw materials, low cost, and no secondary pollution. It can achieve the production of solar fuels and high-value-added chemicals (such as methanol, ethanol, hydrocarbons, etc.) driven by solar energy under normal temperature and pressure conditions, and can truly realize the recycling of carbon, and has great application prospects in the fields of energy and environment.
[0004] However, due to the problems of photocatalytic carbon dioxide reduction technology: a large amount of energy is required to activate chemically stable carbon dioxide molecules, and it is difficult for a single-component photocatalyst to have the characteristics of visible light response, high physical and chemical stability, and high carbon dioxide reduction efficiency, which limits its practical application. Therefore, selecting suitable semiconductor materials with visible light response and strong reduction ability to construct heterojunction composite catalysts is an effective means to improve the efficiency of photocatalytic carbon dioxide reduction. Summary of the invention
[0005] The embodiment of the present invention provides a CN / AgInS 2 A method for preparing a heterojunction composite photocatalyst comprises:
[0006] C 3 N 4 The precursor was sealed and calcined at 400-650°C for at least 4 h, and ground to obtain gC 3 N 4 The powder is dispersed in a hydrochloric acid solution and oil bathed at 60-90°C for at least 4 h, centrifuged, and dried to obtain CN powder;
[0007] The silver source, indium source and thioacetamide powder are dissolved in water at a molar ratio of 1:0.8-1.2:2-5, and a hydrothermal reaction is carried out at 150-190°C for at least 24 hours, followed by centrifugation and drying to obtain AgInS 2 powder;
[0008] CN powder and AgInS 2 The powders were mixed in water at a mass ratio of 1:0.25-2 to prepare a solution, and the solution was dried at 100-300°C to obtain CN / AgInS 2 Heterojunction composite photocatalyst.
[0009] Furthermore, it also includes:
[0010] C 3 N 4 The nanosheet precursor was placed in a crucible, sealed with tin foil, and placed in a tube furnace. The temperature was raised to 450-600°C at a heating rate of 2.5-5°C / min, kept at this temperature for 5-8h, cooled to room temperature at a cooling rate of 0.5-1.5°C / min, and ground to obtain a light yellow gC 3 N 4 powder;
[0011] Take gC 3 N 4 The powder is dispersed in a 0.3-0.6 mol / L hydrochloric acid solution and oil-bathed at 70-85° C. for 5-8 hours. The powder is placed in water, stirred, centrifuged, washed, and dried to obtain CN powder.
[0012] Furthermore, C 3 N 4 The nanosheet precursor is at least one of dicyandiamide, melamine or urea.
[0013] Furthermore, it also includes:
[0014] First, add the silver source and the indium source into deionized water, stir evenly to form a 1.5-2 g / L solution, add thioacetamide and stir evenly to form a precursor solution;
[0015] The precursor solution is transferred into a hydrothermal synthesis reactor and a hydrothermal reaction is carried out at 160-180° C. for at least 24 hours.
[0016] Furthermore, the silver source is AgNO 3 Or one of AgCl.
[0017] Furthermore, the indium source is In(NO 3 ) 3 or InCl 3 One of them.
[0018] Furthermore, CN powder and AgInS 2 The pH of the solution prepared from the powder is adjusted to 4-6, preferably 4.5-5.5, which is used to change the pH value of the solution so that CN and AgInS 2 The surfaces of the particles have different electrical potentials and are attracted together to assemble.
[0019] Furthermore, CN powder and AgInS 2 The powders are in a mass ratio of 1:0.5 to 1.5, preferably 1:1.
[0020] A photocatalytic evaluation method, characterized by comprising:
[0021] The CN / AgInS prepared by any one of the preparation methods of claims 1 to 9 2 The heterojunction composite photocatalyst was added to an acetonitrile / water solution of 10-30 vol% triethanolamine, and CO was introduced into the suspension. 2 Bubble for 30 to 50 minutes to obtain CO 2 Saturated environment;
[0022] The reaction vessel was connected to a dual photocatalytic online reaction evaluation system. After stirring in the system to reach adsorption equilibrium, photocatalytic carbon dioxide reduction was carried out, and the carbon monoxide production was detected to evaluate the carbon dioxide reduction activity of the photocatalyst.
[0023] The beneficial effects of the embodiments of the present invention are:
[0024] 1. The novel CN / AgInS provided by the present invention 2 Heterojunction composite photocatalyst, AgInS by electrostatic self-assembly method 2 The particles were dispersed on the CN nanolayer and a new CN / AgInS 2 Compared with single components, heterojunction materials have strong visible light absorption ability, efficient charge separation ability and enhanced redox ability, which is conducive to achieving efficient photocatalytic carbon dioxide reduction.
[0025] 2. The novel CN / AgInS provided by the present invention 2 Heterojunction composite photocatalyst is a photocatalyst with efficient carbon dioxide reduction active sites. CN and AgInS 2 The close contact between CN / AgInS 2 Charge transfer is achieved at the interface of the heterojunction. 2 When the heterojunction material is formed, electrons are transferred from CN to AgInS 2 Thus, the electron-rich S (2+δ)- site. In the photocatalytic process, CO 2The electron-deficient C atoms in the molecule preferentially adsorb on the electron-rich S (2+δ)- site, then CO 2 The molecule is S (2+δ)- Therefore, the novel CN / AgInS2 heterojunction composite photocatalyst constructed effectively enhances the CO 2 adsorption and activation, thereby improving the photocatalytic carbon dioxide reduction performance of the composite photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 The novel CN / AgInS in Comparative Examples 1-2 and Examples 1-5 of the present invention 2 XRD pattern of heterojunction composite photocatalyst;
[0028] Figure 2 The novel CN / AgInS in Example 1 of the present invention 2 SEM image of heterojunction composite photocatalyst;
[0029] Figure 3 The novel CN / AgInS in Example 1 of the present invention 2 TEM image of heterojunction composite photocatalyst;
[0030] Figure 4 The novel CN / AgInS in Example 1 of the present invention 2 HRTEM image of heterojunction composite photocatalyst;
[0031] Figure 5 The novel CN / AgInS in Comparative Examples 1-2 and Examples 1, 3-4 of the present invention 2 UV-visible diffuse reflectance spectrum of heterojunction composite photocatalyst;
[0032] Figure 6 The novel CN / AgInS in Comparative Examples 1-2 and Examples 1-3 of the present invention 2 Visible light photocatalytic reduction of carbon dioxide activity diagram of heterojunction composite photocatalyst;
[0033] Figure 7 The novel CN / AgInS in Example 1 of the present invention 2 Long-term photocatalytic reduction of carbon dioxide activity diagram of heterojunction composite photocatalyst;
[0034] Figure 8 The novel CN / AgInS in Comparative Examples 1-2 and Example 1 of the present invention 2 Temperature-programmed desorption of carbon dioxide from heterojunction composite photocatalysts; DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0036] Comparative Example 1
[0037] Preparation of CN nanosheets:
[0038] 10g of melamine was added to a clean crucible, which was sealed with aluminum foil and placed in a tube furnace. The temperature was raised to 550°C at a rate of 5°C / min and kept at this temperature for 4 hours. The sample was then cooled to room temperature at a rate of 1°C / min. The obtained light yellow sample was ground and placed in a 0.5mol / L dilute hydrochloric acid solution. The sample was stirred in an oil bath at 80°C for 4 hours. The sample after the oil bath was repeatedly washed with deionized water, centrifuged, dried, and impurities removed to obtain the original gC 3 N 4 powder, named CN, and CN / AgInS 2 Heterojunction composite photocatalysts were used for comparison.
[0039] Comparative Example 2
[0040] Preparation of AgInS 2 Material:
[0041] First, 34 mg of AgNO 3 and 60.2 mg of In(NO 3 ) 3 Add 60 mL of deionized water and stir to form a solution; then add 42 mg of thioacetamide to the above liquid, continue stirring and ultrasonic until the solution is uniform to form a precursor solution; transfer the precursor solution to a hydrothermal synthesis reactor and perform hydrothermal reaction at 180 ° C for 24 hours; the hydrothermal sample is repeatedly washed with deionized water, centrifuged, and dried to obtain AgInS 2 Material.
[0042] Example 1
[0043] Preparation of CN / AgInS 2 Heterojunction composite photocatalyst:
[0044] Take 300 mg of CN and AgInS prepared in Comparative Example 1-2 respectively. 2The sample was uniformly dissolved in 10 mL of deionized water, and a 0.1 mol / L dilute hydrochloric acid solution was used to adjust the pH of the mixed solution to 5.5, and stirred for 10 hours; the mixed solution after stirring was placed in an oven and dried at 100 ° C to obtain CN / AgInS 2 powder, named CA1.
[0045] Embodiment 2-5
[0046] CN / AgInS in Example 2-5 2 The preparation method of the heterojunction composite photocatalyst is the same as that shown in Example 1, except that the indium sulfide silver AgInS 2 The content of AgInS in each embodiment is different. 2 The amount of addition is shown in Table 1. The obtained sample is named CAx (x is AgInS 2 Ratio to CN)
[0047] Table 1. CA1 and AgInS in Examples 1-5 2 Addition amount
[0048] Group CN addition amount <![CDATA[AgInS 2 Add Amount]]> <![CDATA[CN and AgInS 2 Ratio of addition amount of powder]]> Example 1 300mg 300mg 1:1 Example 2 300mg 75mg 1:0.25 Example 3 300mg 150mg 1:0.5 Example 4 300mg 375mg 1:1.25 Example 5 300mg 600mg 1:2
[0049] Sample characterization:
[0050] The CN, AgInS prepared in the comparative examples and examples 2 , CA0.25, CA0.5, CA1, CA1.25 and CA2 were characterized to obtain Figure 1 The XRD pattern shown in Figure 2 SEM shown, as Figure 3 and Figure 4 The TEM and HRTEM images shown and Figure 5 The UV-vis graph shown in the figure. Among them, the XRD test was completed by the X-ray powder diffractometer (RigakuSmartLab 9kW) of Japan Rigaku, the SEM test was completed by the scanning electron microscope (ZEISS Gemini300) of Germany Zeiss; the TEM and HRTEM tests were completed by the field emission transmission electron microscope (TMO TalosF200X) of the Thermo Fisher Scientific, and the UV-vis test was completed by the ultraviolet spectrophotometer (Shimadzu, UV-2600) of Japan Shimadzu.
[0051] The CA1 prepared in Example 1 is taken as an example for description.
[0052] Depend on Figure 1In the XRD patterns shown, characteristic peaks belonging to the (002) crystal plane of carbon nitride and characteristic peaks belonging to the (002), (040), (320) and (042) crystal planes of indium silver sulfide can be observed simultaneously in all heterojunction samples, indicating that CN and AgInS 2 Successfully constructed CN / AgInS composite 2 Heterojunction composite photocatalyst. Figure 2 and Figure 3 It can be observed that CN has a large-scale layered stacking structure, while AgInS 2 It is a bulk crystal structure with an average size of about 200 nm. 2 The particles are randomly distributed on the surface and edge of the CN layer, indicating that the CN layer and AgInS 2 The particles are tightly bound together by electrostatic adsorption. Figure 4 AgInS can be observed in high-resolution transmission electron microscopy. 2 The lattice fringes of AgInS 2 The (002) crystal plane of CN and AgInS 2 The organic / inorganic interface between them is the key to successfully constructing CN / AgInS 2 Heterojunction provides strong evidence. Figure 5 The UV-visible diffuse reflectance spectrum is shown, and it can be seen that compared with carbon nitride, the composite photocatalytic material exhibits stronger light absorption ability in the range of 300-1000nm. Photocatalytic carbon dioxide reduction performance test:
[0053] The carbon dioxide reduction performance test of the photocatalyst prepared in this example adopts a dual photocatalytic online reaction evaluation system, which is a gas chromatograph (Shimadzu-Nexis GC 2030) of Shimadzu Corporation of Japan combined with an all-glass automatic online trace gas analysis system (PLS-Labsolar 6A) of Beijing Perfect Light Technology Co., Ltd., and the light source used is a 300w xenon lamp light source (PLS-SXE300 / 300UV) of Beijing Perfect Light Technology Co., Ltd.
[0054] The specific steps are as follows:
[0055] 20 mg of the catalyst was added to 50 ml of acetonitrile / water solution containing 20 vol% triethanolamine, and a suspension was obtained by ultrasonic dispersion. CO was introduced into the suspension. 2 Bubble for 30 min to obtain CO 2Saturated environment. Connect the reaction vessel to the dual photocatalytic online reaction evaluation system, stir in the system to reach adsorption equilibrium, and then perform the photocatalytic carbon dioxide reduction performance test. Detect the carbon monoxide production every 1 hour to evaluate the carbon dioxide reduction activity of the photocatalyst.
[0056] The experimental results show that the carbon monoxide yield of the CA1 heterojunction composite photocatalyst reaches 121.08 μmol·h after 5 hours of illumination. -1 ·g -1 , with high photocatalytic carbon dioxide reduction activity. Figure 6 Shows different AgInS 2 Effect of addition amount on the carbon dioxide reduction performance of composite photocatalyst. Figure 6 It can be seen that the addition of AgInS 2 After that, the carbon dioxide reduction activity of the composite photocatalyst was compared with that of CN and AgInS 2 The substrate material has been significantly enhanced. In addition, AgInS 2 The addition amount and the carbon dioxide reduction performance of the composite photocatalyst show a volcano-shaped relationship. 2 When the mass ratio of CN to N is 1:1, the carbon dioxide reduction performance of the composite photocatalyst reaches the highest. When the loading amount continues to increase, its carbon dioxide reduction performance decreases.
[0057] Figure 7 The activity graph of carbon monoxide production of the composite photocatalyst over time is given. Figure 7 It can be seen that as time goes by, the carbon monoxide production of the composite photocatalyst continues to increase and tends to be stable after 10 hours.
[0058] Carbon dioxide adsorption capacity test:
[0059] Figure 8 The temperature-programmed desorption of carbon dioxide is given, and the CA1 heterojunction composite photocatalyst is better than CN and AgInS 2 It has stronger carbon dioxide chemical adsorption ability, which indicates that the construction of CN / AgInS 2 Heterojunction can improve CO 2 The adsorption and activation ability of the photocatalyst is beneficial to its photocatalytic carbon dioxide reduction.
[0060] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
[0061] The above descriptions are only some embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a CN / AgInS2 heterojunction composite photocatalyst, characterized in that: include: The C3N4 precursor is sealed and calcined at 400-650°C for at least 4 hours, ground to obtain g-C3N4 powder, dispersed in a hydrochloric acid solution, and oil bathed at 60-90°C for at least 4 hours, centrifuged, and dried to obtain CN powder; The silver source, indium source and thioacetamide powder are dissolved in water at a molar ratio of 1:0.8-1.2:2-5, and a hydrothermal reaction is carried out at 150-190° C. for at least 24 hours, followed by centrifugation and drying to obtain AgInS2 powder; CN powder and AgInS2 powder are mixed in a mass ratio of 1:0.25-2 in water to prepare a solution, and the solution is dried at 100-300° C. to obtain a CN / AgInS2 heterojunction composite photocatalyst.
2. The preparation method according to claim 1, characterized in that: Also includes: The C3N4 nanosheet precursor is placed in a crucible, sealed with tin foil, placed in a tube furnace, heated to 450-600°C at a heating rate of 2.5-5°C / min, kept at this temperature for 5-8h, cooled to room temperature at a cooling rate of 0.5-1.5°C / min, and ground to obtain a light yellow g-C3N4 powder; Disperse g-C3N4 powder in 0.3-0.6 mol / L hydrochloric acid solution, and place in an oil bath at 70-85°C for 5-8 hours. Place the powder in water, stir, centrifuge, wash, and dry to obtain CN powder.
3. The preparation method according to claim 2, characterized in that: The precursor of the C3N4 nanosheet is at least one of dicyandiamide, melamine or urea.
4. The preparation method according to claim 1, characterized in that: Also includes: First, add the silver source and the indium source into deionized water, stir evenly to form a 1.5-2 g / L solution, add thioacetamide and stir evenly to form a precursor solution; The precursor solution is transferred into a hydrothermal synthesis reactor and a hydrothermal reaction is carried out at 160-180° C. for at least 24 hours.
5. The preparation method according to claim 1, characterized in that: The silver source is one of AgNO3 or AgCl.
6. The preparation method according to claim 1, characterized in that: The indium source is one of In(NO3)3 or InCl3.
7. The preparation method according to claim 1, characterized in that: The pH of the solution made of CN powder and AgInS2 powder is adjusted to 4-6.
8. The preparation method according to claim 1, characterized in that: The mass ratio of CN powder to AgInS2 powder is 1:0.5 to 1.5, preferably 1:
1.
9. The preparation method according to claim 7, characterized in that: The pH of the solution made of CN powder and AgInS2 powder was adjusted to 4.5-5.
5.
10. A photocatalytic evaluation method, characterized in that: include: Add the CN / AgInS2 heterojunction composite photocatalyst prepared by any one of the preparation methods of claims 1 to 9 to an acetonitrile / water solution of 10-30 vol% triethanolamine, and bubble CO2 into the suspension for 30 to 50 minutes to obtain a CO2 saturated environment; The reaction vessel was connected to a dual photocatalytic online reaction evaluation system. After stirring in the system to reach adsorption equilibrium, photocatalytic carbon dioxide reduction was carried out, and the carbon monoxide production was detected to evaluate the carbon dioxide reduction activity of the photocatalyst.